2013
DOI: 10.1007/s40435-013-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of TB with the effects of case detection and treatment

Abstract: In this paper a non-linear mathematical model of tuberculosis with case detection and treatment is proposed and analyzed. The whole population under consideration is divided into four compartments e.g. susceptible, exposed, infected and Recovered to study the transmission dynamics of the tuberculosis. Based on the immunity level, susceptible individuals move to exposed class or directly to infected class once they come into contact with an infective. This has been incorporated through progression rate which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…The analysis focused on the applications of dynamical systems methods and optimal control theory to the epidemiology of TB. In agreement with the earlier studies on TB models with exogenous re‐infection property (see, for examples, References 3,4,6,9, and 13), it was shown that the autonomous deterministic TB model exhibits backward bifurcation whether incomplete treatment property is present or not. The occurrence of backward bifurcation in TB transmission dynamics makes the disease control more taxing.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The analysis focused on the applications of dynamical systems methods and optimal control theory to the epidemiology of TB. In agreement with the earlier studies on TB models with exogenous re‐infection property (see, for examples, References 3,4,6,9, and 13), it was shown that the autonomous deterministic TB model exhibits backward bifurcation whether incomplete treatment property is present or not. The occurrence of backward bifurcation in TB transmission dynamics makes the disease control more taxing.…”
Section: Resultssupporting
confidence: 90%
“…The existence of two endemic equilibria in item (iii) of Theorem 2 shows that the TB model () has the potential to exhibit backward bifurcation property (a situation where the stable DFE and stable EE exist simultaneously when 0<1), which can be caused by exogenous re‐infection of latently‐infected individuals. This result has been well‐established in literature on TB dynamics (see References 3‐5, and 9).…”
Section: Analysis Of Tb Model Without Controlssupporting
confidence: 80%
See 2 more Smart Citations
“…ese models apply to di erent types of populations such as a city or country, a school, prison, or refugee camp, see for instance, [8,9] Also, di erent models would focus on various factors such as progression rate, treatment, vaccination, immigration, etc. see [10][11][12].…”
Section: Introductionmentioning
confidence: 99%